Econet of South Besarabia (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
A scheme of the econet of South Besarabia has been developed. Covering of especially environmentally valuable locations of the region with natural vegetation by the econet's ecosystems, stimulation of settling conditions and migration of species as well as guaranteeing of their restoration, conservation and protection of their habitats is its destination. Special significance is that it is developed for the region with environmentally vulnerable and excessively degraded ecosystems. A floristic and phytocoenotic characteristic of the econet's components is represented in the article.
Keywords: econet, key areas, natural cores, ecocorridor, vegetation, rare species, rare syntaxa, anthropogenous factors.